Cytotoxic lymphocyte effector function is unaffected in patients with Gaucher disease - Zou, Jinyun; Noori, Tahereh; Walterfang, Mark; Szer, Jeff; Trapani, Joseph A.; Voskoboinik, Ilia (Frontiers in Immunology, 2025)
Gaucher disease (GD) is one of the most common lysosomal storage disorders. It is caused by bi-allelic mutations in the GBA1 gene responsible for the production of β-glucocerebrosidase, an enzyme responsible for the hydrolysis of the sphingolipid glucocerebroside. This results in its accumulation in various organs, and patients can present with a variety of symptoms ranging from visceral enlargement, bone pathology and hematological manifestations. Neuronopathic effects are seen in the severe form of the disease. GD patients also have an increased risk of B-cell malignancies. Some of the hematological symptoms of GD resemble those of the systemic hyperinflammatory condition, hemophagocytic lymphohistiocytosis (HLH). HLH can be familial, due to functional deficiencies in cytotoxic lymphocytes, or acquired from a variety of causes ranging from infections to blood cancers. While patients with inherited and acquired HLH receive the same first-line therapy, patients with the familial form can only be cured by stem cell transplantation, although this treatment may be detrimental to patients with the acquired form of the disease. Therefore, we investigated whether the abnormal lipid accumulation in GD patient cytotoxic lymphocytes and in cells with irreversibly inhibited glucocerebrosidase activity affects their cytotoxicity. Our detailed analysis of primary cytotoxic T lymphocytes and natural killer cells revealed that the activity of these cells was not affected. This finding has important implications for the treatment choices for patients with GD and suggests that these patients can be treated with autologous immunotherapy if they develop hematological cancers.